Codeless Development of a Customized SMILE Nomogram Using a Large Language Model: A Practical Framework for Clinicians - Hye Won Jun; Sun Young Ryu; Tae Keun Yoo (Journal of Ophthalmology, 2025)
Conclusion: ChatGPT-4 not only provides a statistical model for SMILE nomograms but also creates a calculator for user convenience. Clinicians can easily build their own nomogram calculators using only the collected data without coding. The advanced LLM will allow clinicians to conveniently create customized nomogram tools.